Identification of wild edible plants used by the Orang Asli, indigenous peoples of the Malay Peninsula - Tharmabalan, Rachel Thomas (Frontiers in Sustainable Food Systems, 2023)
Background This research focused on the different varieties of wild edible plants (WEPs) actively utilized by the Orang Asli of Malaysia and their medicinal values. The Orang Asli have been relying on these plants for their sustenance and wellbeing. However, with environmental degradation, many of these wild edibles are slowly becoming sparse, which then has a spillover effect and has resulted in the erasure of knowledge. Therefore, this research paper also aims to highlight the naming system utilized by the Orang Asli, the gender/age gap and the medicinal properties of these wild edible plants. Methods This research was conducted to identify the important wild edibles used among the Orang Asli, using both semi-structured and field interviews, as well as ethnobotanical appraisal methods. With the assistance of 24 informants, a total of nine wild edible plants were identified based on their importance as food and medicine for the Orang Asli groups in three different Semai settlements. Results and discussion From the results obtained, the wild edibles identified in the study have potential medicinal value and have been used by the Orang Asli for many generations. Also, based on my results, older Orang Asli can potentially serve as a repository of knowledge of wild edible plants within their settlements, as they were more informed than young people. However, there is little remaining knowledge of their medicinal uses in Telimau; elder women retain more knowledge than elder men in Bukit Terang, and the greatest knowledge retention for both young and old is seen in the more remote settlement of Kampung Sat. Conclusion This research documents the medicinal uses of these wild edibles, and may provide a starting point for further studies on these species and encourage conservation initiatives, in addition to helping safeguard the indigenous knowledge and the distinct cultural identities of the Orang Asli.